Perovskite solar cells : technology and practices - Fu, Kunwu; Ho-Baillie, Anita (Anita Wing Yi); Mulmudi, Hemant Kumar; Pham, Thi Thu Trang (Sandy) (Toronto ; New Jersey : Apple Academic Press, 2019)
'Key features: Provides an update on a hot trending topic of renewable energy and energy conversion technologies ; Introduces emerging materials processing methods of PSCs ; Covers electron-transporting layers in PSCs, hole-transporting layers in PSCs, and lead-free PSCs ; Includes easy-to-understand diagrams and configurations ; Serves as a quick guide on PSCs for young researchers'--
Includes bibliographical references and index.
Keywords: Perovskite solar cells; Solar cells -- Materials; Photovoltaic cells -- Materials